Abstract 12250: Trends in Retractions of Peer Reviewed Literature: Comparison Between Cardiology and Other Medical Specialties - Wadhwa, Raoul R; Rasendran, Chandruganesh; Popovic, Zoran B; Nissen, Steven E; Desai, Milind Y (Circulation (New York, N.Y.), 2021)
IntroductionPeer-reviewed manuscript retractions are increasingly being recognized, wasting valuable scientific resources and magnifying false conclusions. The temporal trend and downstream impact of retracted cardiology articles on research and knowledge dissemination remain largely unexplored. We sought to compare retraction trends between cardiology and clinical medicine overall. MethodsWe conducted a systematic review of retracted publications using the Retraction Watch database. Articles were selected based on manual classification. The Welch two-sample t-test and Mann-Kendall trend test were used for statistical inference. ResultsOut of 22,740 articles, 6,594 (29%) and 445 (2%) were related to medicine overall and cardiology, respectively. The ratio of retractions to published articles has increased over recent years for medicine overall and cardiology (Figure upper panel, p < 0.01 for trends). Relative to 1990 levels, retractions in medicine have increased at over double the rate in comparison to cardiology (p < 0.01 for rate difference). There has been a downward trend in the time between publication and retraction for articles in cardiology and medicine (Figure lower panel, p < 0.01 for trends). There was no significant difference in time to retraction between the two fields. ConclusionsWe report a sharp increase in the retracted articles in the medical literature over time. Although retractions in cardiology are increasing, they are doing so at a slower rate than other specialties. Sharing research guidelines from cardiology to other medical specialties could improve their retraction statistics, thus decreasing patient harm and waste of valuable scientific resources. Retractions are being identified earlier, potentially due to improved policing of the published literature. However, more stringent quality checks should occur during the peer review processes to prevent eventually retracted articles from being published.